Analisis Yuridis Pencabutan Hak-Hak Politik Pelaku Tindak Pidana Korupsi (Studi Putusan Mahkamah Agung RI Nomor 113 K/PID.SUS/2020) - Brimen Begni Gudmen Sihotang (Jurnal Smart Hukum (JSH), 2023)
Eradicating the crime of corruption must apply strict sanctions in order to provide a deterrent effect for corruptors, as well as being expected to reduce anyone from committing corruption. One of the latest breakthroughs is to apply additional criminal sanctions for revocation of certain rights. The formulation of the problem in this thesis is how the legal arrangements for the revocation of political rights against perpetrators of criminal acts of corruption, how criminal responsibility for perpetrators of criminal acts of corruption, how the legal considerations of judges on the revocation of political rights against perpetrators of criminal acts of corruption. The research method used is descriptive analysis that leads to normative juridical legal research, namely research conducted by referring to legal norms, namely researching library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The legal regulation on the revocation of political rights in the form of the right to be elected in public office is the implementation of the application of criminal sanctions that are extraordinary enforcement as regulated in Article 17 of the Law of the Republic of Indonesia Number 31 of 1999 in conjunction with the Law of the Republic of Indonesia Number 20 of 2001 concerning Eradication Corruption crimes may be subject to additional penalties as referred to in Article 18 paragraph (1) letter d and Article 10 letter b number 1 of the Criminal Code concerning additional penalties. The results of the study indicate that the judge's legal considerations for the revocation of political rights against perpetrators of criminal acts of corruption are criminal acts committed cannot be a good example. At the end of its decision, the Panel of Judges imposed an additional penalty on the Defendant in the form of revocation of the right to be elected in public office for 3 (three) years after the Defendant had finished serving his main sentence.